Odor intolerance and proposed off-site limit under the Thailand public health provision - Taiyatach Hirunrueng; Withida Patthanaissarnukool; Tanasri Sihabut (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - This study aimed to determine the initial odor concentration which commonly urges Thais to make complaints and to propose an off-site limit for odorous emissions. Design/methodology/approach - Odor concentrations measured by Nasal Rangers® and face-to-face survey interviews were simultaneously conducted with 122 residents located near 101 manufacturing centers in 20 provinces of Thailand. Along with the measured values and odor strength verbally rated by trained assessors, the number of complaint intentions, annoyance levels and health symptoms of residents were reported. Findings - The odor concentrations in the inspected houses were <2, 2, 4, 7, 15, 30 and 60 D/T. The trained assessors stated that at the concentration of 4D/T, most odors were likely to be objectionable and unbearable when odor concentrations were higher. Correspondingly, about 80% of residents exposed to odors at this level felt some annoyance and reported health symptoms and therefore intended to register a complaint. At lower concentrations, the annoyance level as well as the decision to complain likely depended on other factors such as hedonic tone and exposure frequency. Practical implications - The proposed off-site reference value for odor complaint assessment was 4D/T. However, in the case of lower concentrations, additional relevant factors were crucially required to investigate the complaint. Originality/value - This finding will help local authorities diminish subjective discretion on whether or not an odor constitutes a nuisance.